(untitled) (Annals of Medical Research, 2021)
The hernia is called the protrusion of the intra-abdominal organs out of a defect in the abdominal wall. Although the contents of the hernial sac generally form the omentum and small intestines, it can be found in organs such as appendix, fallopian tubes, ovary, bladder, Meckel diverticulum in the hernial sac. Although ultrasonographic imaging is helpful in determining the contents of the hernia sac, surprise sac contents may still be encountered during surgery. In this case report, a 38-year-old female patient with a ruptured ovarian cyst in the incarcerated hernia sac is discussed with the literature.